'Toothbrush' plant bugs and allies: Protemiris gen. nov., a new genus and five new species of Proteaceae‐associated Australian Phylinae (Hemiptera : Miridae). Issue 1 (20th July 2016) - Russell, Kaleigh; Weirauch, Christiane
Abstract: Due to substantial recent field and taxonomic research, the true biodiversity of plant bugs in the subfamily Phylinae in Australia is only beginning to emerge. This study is a contribution to advancing our understanding of the diversity of plant bugs in Australia. A new genus and five new species of Australian Phylinae are here described, where all species are associated with host plants in the Proteaceae, a family of plants with few well‐documented plant bug associates. The new genus Protemiris gen. nov. and the new species P . adenanthi sp. nov., P . conospermi sp. nov., P . distichi sp. nov., P . grevillae sp. nov. and P . isopogoni sp. nov. are mostly restricted to Western Australia, with one species also occurring in the Northern Territory. A morphology‐based cladistic analysis confirms the monophyly of this new genus and places it in the recently described subtribe Exocarpocorina of the tribe Semiini, among other Australian phylines with similarly elaborate male and female genitalia. Habitus and scanning electron images, genitalic illustrations, host associations and distribution maps for the new plant bug species are provided.